2019
DOI: 10.1016/j.isci.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Control Architecture of Complex Brain Networks

Abstract: Summary The brain controls various cognitive functions in a robust and efficient way. What is the control architecture of brain networks that enables such robust and optimal control? Is this brain control architecture distinct from that of other complex networks? Here, we developed a framework to delineate a control architecture of a complex network that is compatible with the behavior of the network and applied the framework to structural brain networks and other complex networks. As a result, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…Cognitive faculties rely on the cerebral cortex, a complex structural and functional region of the brain that contains the discrete elements that support information processing and computation. However, specific cognitive functions are associated with the coordinated activation of different brain regions [38]. Although we know the structural interconnectivity among the different brain regions, we do not understand the fundamental mechanisms that drive the coordinated functional interplay among specific brain regions and how this interplay results in the expression of different cognitive processes.…”
Section: Structural-functional Relationship In the Neocortexmentioning
confidence: 98%
See 2 more Smart Citations
“…Cognitive faculties rely on the cerebral cortex, a complex structural and functional region of the brain that contains the discrete elements that support information processing and computation. However, specific cognitive functions are associated with the coordinated activation of different brain regions [38]. Although we know the structural interconnectivity among the different brain regions, we do not understand the fundamental mechanisms that drive the coordinated functional interplay among specific brain regions and how this interplay results in the expression of different cognitive processes.…”
Section: Structural-functional Relationship In the Neocortexmentioning
confidence: 98%
“…The use of tractography and constructed structural brain networks in healthy humans have shown a hidden distributed and overlapping control architecture that brings high efficiency in the transition among network states supporting cognitive functions as well as giving robustness against damage [38]. This hidden brain structure seems to be supported by a minimal subset of dominating nodes that control the remaining nodes with one-step direct interaction [38].…”
Section: Structural-functional Relationship In the Neocortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Control theories for complex networks including biological networks have been actively investigated recently 28–34 . Liu, Slotine and Barabási showed that we can control a variety of complex networks by controlling the driver nodes that are identifiable from the network structures 35 .…”
Section: Introductionmentioning
confidence: 99%
“…The functional role of single regions composing the DAN network has been extensively investigated by applying single-node TMS, and then assessing effects in terms of brain activity changes in that node Sack et al, 2005Thut et al, 2005) as well as at a network level Sack et al, 2005Sack et al, , 2007. Since by nature these nodes interact with one another (Cocchi et al, 2013;Lee et al, 2019), the effects of stimulation are not contained within the area that is stimulated, but also affect interconnected regions within the same network (Bestmann et al, 2008;Feredoes et al, 2011;Ilmoniemi et al, 1997;Morishima et al, 2009;Ruff et al, 2008;Sack et al, 2007;Werf et al, 2010) or regions of other overlapping networks (Chen et al, 2013;Gratton et al, 2013;Lee et al, 2019). The fact that the stimulation is not limited to the targeted area can lead to many interpretational problems.…”
Section: Distilling Facilitation and Inhibition After The Inhibition Of Left And Right Fefsmentioning
confidence: 99%